Perception of and adaption to climate change: the case of groundnut production of costal island in Bangladesh - Begum, Ratna; Ame, Atia Sharmin; Ethen, Dilshad Zahan (Frontiers in Climate, 2025)
IntroductionNut farming in the island regions of Bangladesh faces considerable challenges due to climate change. This research investigates the climate change perceptions and adaptive capacity of strategies of male and female groundnut farmers in island of Hatiya, Bangladesh where nut yields fall below the national average.MethodsData were gathered from 170 male and 130 female farmers on the island, with Chi-square tests used to analyze gender-based differences in perceptions of climate change and adaptive capacity. A probit regression model was applied to evaluate the factors driving the adoption of these strategies.Results and discussionThe findings suggest that male and female farmers largely share similar perceptions of climate change impacts, such as changes in rainfall patterns, increased pest infestations, and a greater need for fertilizers. Consequently, a combined analysis of both genders was conducted to identify the factors influencing adaptive capacity of strategies. Additionally, the results indicated that older farmers are more likely to engage in off-farm activities as a strategy to cope with environmental uncertainties. Education and farming experience are key factors in driving crop diversification and climate-smart practices, with farmers adjusting planting dates, shifting crops, and using weather forecasts as the most common adaptive capacity. Less frequently adopted strategies include agroforestry and urban migration. Education and farming experience are positively associated with the adoption of proactive adaptive capacity, thereby improving farmers’ ability to cope with climate change. This study exploring adaptive capacity of nut farmers in Bangladesh’s island and suggests interventions to enhance resilience and encourage sustainable agricultural practices in response to climate change.